2015
DOI: 10.1038/srep14531
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl acetate fraction of Amomum xanthioides improves bile duct ligation-induced liver fibrosis of rat model via modulation of pro-fibrogenic cytokines

Abstract: We investigated anti-hepatofibrotic effects of ethyl acetate fraction of Ammomum xanthoides (EFAX) using bile duct ligation (BDL)-induced hepatic fibrosis in a rat model. Male SD rats (6 weeks old) underwent BDL followed by 15 days of orall administration of EFAX (12.5, 25 or 50 mg/kg) or ursodeoxycholic acid (25 mg/kg). BDL caused animal death, ascites formation, alterations in serum biochemistries, and severe hepatic injury with excessive collagen deposition, whereas EFAX treatment significantly attenuated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In addition, the fruit is effective against asthma and also functions as an antiemetic agent (7). Various studies have demonstrated that the seed extract of A. xanthioides (AXE) exerts various pharmacological effects, including hepatoprotective and anti-gastritis effects, and the prevention of diabetes mellitus (8,9). Furthermore, our previous studies demonstrated that seed AXE inhibited immediate-type hypersensitivity by reducing mast cell degranulation (10,11).…”
Section: Anti-inflammatory Effect Of Amomum Xanthioides In a Mouse Atmentioning
confidence: 99%
“…In addition, the fruit is effective against asthma and also functions as an antiemetic agent (7). Various studies have demonstrated that the seed extract of A. xanthioides (AXE) exerts various pharmacological effects, including hepatoprotective and anti-gastritis effects, and the prevention of diabetes mellitus (8,9). Furthermore, our previous studies demonstrated that seed AXE inhibited immediate-type hypersensitivity by reducing mast cell degranulation (10,11).…”
Section: Anti-inflammatory Effect Of Amomum Xanthioides In a Mouse Atmentioning
confidence: 99%
“…Inhibition of matrix metalloproteinases (MMPs) results in reduced ECM degradation 3 . Controlling the activation of HSCs that occurs during hepatic fibrosis may have a therapeutic benefit 4 7 .…”
Section: Introductionmentioning
confidence: 99%
“…CCl 4 is a laboratory reagent characterized by toxicity causing liver damage and liver fibrosis and is extensively used in liver-related studies 17 . Bile duct ligature (BDL) impairs bile formation and bile flow, leading to cholestatic liver injury that progresses to hepatic fibrosis and cirrhosis 7 . Animal models of liver cirrhosis are widely used to study the mechanisms underlying liver fibrosis and the effect of various drugs on its progression 18 – 21 .…”
Section: Introductionmentioning
confidence: 99%
“…This formula evidenced the hepatoprotective and anti-hepatofibrotic effects in dimethylnitrosamine-induced chronic hepatic injury rat model and non-alcoholic steatohepatitis mouse model Lee et al, 2018). Those three medicinal plants also have been proved to have the hepatoprotective effects or antioxidative property in animal-based experiments (Han et al, 2012;Kim et al, 2014;Kim et al, 2015).…”
Section: Introductionmentioning
confidence: 88%
“…xanthioides was also reported from a chronic liver injury model (Wang et al, 2013). Furthermore, S. miltiorrhiza showed the neuroprotective actions against the psychological stress (Kim et al, 2015). Quercitrin, a main chemical compound in CG plus was known to modulate macrophage activity by inhibition of peroxynitrite production (Kim et al, 2007).…”
Section: A B C Dmentioning
confidence: 99%